Solid electrolyte, negative electrode mixture, battery, and method for producing battery
By using sulfide solid electrolytes with specific dimensions and fracture energies, the cracking and peeling problems of electrode layers and solid electrolyte layers in batteries were solved, thereby achieving suppression of battery resistance and improvement of the stability of conduction pathways.
Patent Information
- Application Number
- CN202411187700.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-07
AI Technical Summary
In a battery, the expansion and contraction of the electrode layer due to charging and discharging can lead to cracking and peeling of the electrode layer and the solid electrolyte layer, increasing the battery resistance.
A sulfide solid electrolyte with specific size and fracture energy, combined with the characteristics of low crystallinity and high Li ion conductivity, is used in the negative electrode composite to suppress cracking and peeling of the electrode layer and the solid electrolyte layer.
It effectively suppresses the increase in battery resistance, maintains good ion and electron conduction pathways, and improves the performance stability of the battery.
Smart Images

Figure CN119581647A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte, a negative electrode composite material and a battery containing the solid electrolyte, and a method for manufacturing the battery. Background Art
[0002] A battery generally includes a negative electrode current collector, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector.
[0003] For example, Patent Document 1 discloses that an all-solid lithium battery is produced using a negative electrode slurry containing a silicon-based active material, a sulfide solid electrolyte, styrene butadiene rubber, and a dispersion solvent.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-125468 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In a battery, the electrode layer may expand and contract due to charge and discharge. In the case of repeated charge and discharge, cracks (cracks) may occur in the electrode layer and the solid electrolyte layer, and peeling of the electrode layer and the solid electrolyte layer may occur. If cracking and peeling occur, the battery resistance may increase because the ion conduction path and the electron conduction path are cut off. Therefore, from the perspective of improving battery performance, it is necessary to suppress cracking and peeling and suppress the increase in battery resistance.
[0009] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide a solid electrolyte capable of suppressing an increase in battery resistance.
[0010] Means for solving problems
[0011] [1] A solid electrolyte, wherein the fracture energy when formed into pellets having a length of 5 mm in the X-axis direction, a length of 20 mm in the Y-axis direction, and a length of 1 mm in the Z-axis direction is greater than 21.4×10 3 kJ / m 3 .
[0012] [2] The solid electrolyte according to [1], wherein the fracture energy is 34.2×10 3 kJ / m 3 above.
[0013] [3] The solid electrolyte according to [1] or [2], wherein the fracture energy is 75.0×10 3 kJ / m3 the following.
[0014] [4] The solid electrolyte according to any one of [1] to [3], wherein the solid electrolyte is a sulfide solid electrolyte.
[0015] [5] The solid electrolyte according to [4], wherein the sulfide solid electrolyte contains Li element, A element, and S element, and A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In.
[0016] [6] The solid electrolyte according to [4] or [5], wherein the sulfide solid electrolyte contains Li element, P element and S element.
[0017] [7] A negative electrode composite material comprising a negative electrode active material and a solid electrolyte, wherein the solid electrolyte is the solid electrolyte described in any one of [1] to [6].
[0018] [8] The negative electrode composite material according to [7], wherein the negative electrode active material is a Si-based active material.
[0019] [9] A battery comprising a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, wherein at least one of the positive electrode active material layer, the negative electrode active material layer and the electrolyte layer contains the solid electrolyte described in any one of [1] to [6].
[0020]
[10] A method for manufacturing a battery, comprising: a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, the method comprising a negative electrode active material layer forming step of forming the negative electrode active material layer using a negative electrode composite material containing a negative electrode active material and an electrolyte, wherein the electrolyte is a solid electrolyte described in any one of [1] to [6].
[0021] Effects of the Invention
[0022] The present disclosure achieves the effect of being able to suppress an increase in battery resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic perspective view illustrating a pellet in the present disclosure.
[0024] Figure 2 This is a schematic cross-sectional view illustrating a battery in the present disclosure.
[0025] Figure 3 It is a graph showing the relationship between the fracture energy and the battery resistance in Examples and Comparative Examples.
[0026] Description of Reference Numerals
[0027] 1…Positive electrode active material layer
[0028] 2…Negative electrode active material layer
[0029] 3…Electrolyte layer
[0030] 4…Positive electrode collector
[0031] 5…Negative electrode collector
[0032] 10…Battery DETAILED DESCRIPTION
[0033] Hereinafter, the solid electrolyte, the negative electrode composite material and the battery containing the solid electrolyte, and the method for producing the battery in the present disclosure will be described in detail.
[0034] A. Solid Electrolyte
[0035] like Figure 1 As shown in FIG. 1 , the breaking energy of the solid electrolyte disclosed in the present invention when formed into a pellet with a length of 5 mm in the X-axis direction, a length of 20 mm in the Y-axis direction, and a length of 1 mm in the Z-axis direction is greater than 21.4×10 3 kJ / m 3 .
[0036] According to the present disclosure, since the fracture energy ratio of the pellets when formed into a specified size is 21.4×10 3 kJ / m 3 Therefore, even if the electrode layer (active material layer) expands and contracts due to the charge and discharge of the battery, it is believed that the cracking and peeling of the electrode layer and the solid electrolyte can be suppressed. As a result, a good ion conduction path and an electron conduction path can be maintained, and the increase in battery resistance can be suppressed.
[0037] At a filling rate (filling rate of solid electrolyte in pellets) of 100%, the fracture energy can be 34.2×10 3 kJ / m 3 Above, it can also be 51.3×10 3 kJ / m 3 On the other hand, the fracture energy is, for example, 75.0×10 3 kJ / m 3 Below, can be 70.0×10 3 kJ / m 3 Below, it can be 67.9×10 3 kJ / m 3 the following.
[0038] The fracture energy can be measured by the method described in the examples.
[0039] The solid electrolyte preferably has a low crystallinity. This is because, as described in the examples described later, a solid electrolyte having a low firing temperature when making a solid electrolyte, that is, a solid electrolyte having a low crystallinity, shows good fracture energy. It is speculated that this is because the crystallinity of the solid electrolyte affects the strength of the interface bonding between the solid electrolytes in the pellets.
[0040] The crystallinity of the solid electrolyte is, for example, 80% or less, 70% or less, 60% or less, or 50% or less. On the other hand, the crystallinity is, for example, 5% or more, 10% or more, or 30% or more. The crystallinity may be a value obtained by an X-ray diffraction method. In addition, the crystallinity may be a value obtained by a differential scanning calorimeter (DSC).
[0041] It is preferred that the solid electrolyte have a high Li ion conductivity. The Li ion conductivity of the solid electrolyte at 25°C is, for example, 1×10 -4 S / cm or more, preferably 1×10 -3 S / cm or more. The solid electrolyte preferably has high insulation properties. The electronic conductivity of the solid electrolyte at 25°C is, for example, 10 -6 S / cm or less, can be 10 -8 S / cm or less, can be 10 -10 S / cm or less. In addition, as the shape of the solid electrolyte, for example, a particle shape can be cited. The average particle size (D 50 ) is, for example, 0.1 μm or more and 50 μm or less. 50 ) refers to the cumulative 50% particle size in a volume-based particle size distribution using a laser diffraction particle size distribution measuring apparatus.
[0042] As solid electrolytes, inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and nitride solid electrolytes, and organic solid electrolytes such as polymer electrolytes can be cited. Among these, sulfide solid electrolytes are preferred because they have high Li ion conductivity.
[0043] The sulfide solid electrolyte preferably contains sulfur (S) as the main component of the anion element. The oxide solid electrolyte preferably contains oxygen (O) as the main component of the anion element. The nitride solid electrolyte preferably contains nitrogen (N) as the main component of the anion element.
[0044] The sulfide solid electrolyte preferably contains, for example, Li element, A element (A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga and In), and S element. In addition, the sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element and I element.
[0045] The sulfide solid electrolyte preferably has an anionic structure of ortho composition (e.g., PS4 3- Structure, SiS4 4- Structure, GeS4 4- Structure, AlS3 3- Structure or BS3 3- The main component of the anion structure is a sulfide solid electrolyte. This is because the chemical stability is high. The proportion of the anion structure of the original composition relative to the total anion structure in the sulfide solid electrolyte is, for example, 70 mol% or more, and can be 90 mol% or more.
[0046] The sulfide solid electrolyte may have a crystal phase. Examples of the crystal phase include a Thio-LISICON type crystal phase, an LGPS type crystal phase, and an Argentum type crystal phase.
[0047] There is no particular limitation on the composition of the sulfide solid electrolyte, and examples thereof include xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30).
[0048] Examples of oxide solid electrolytes include perovskite-type solid electrolytes such as (Li, La)TiO3, and examples of nitride solid electrolytes include Li3N and Li3N-LiI-LiOH.
[0049] Examples of the polymer electrolyte include polyethylene oxide (PEO) and polypropylene oxide (PPO).
[0050] B. Negative electrode composite material
[0051] The negative electrode composite material contains a negative electrode active material and the above-mentioned solid electrolyte. The solid electrolyte is as described in "A. Solid Electrolyte".
[0052] The negative electrode active material is not particularly limited, and examples thereof include Li-based active materials such as metallic lithium and lithium alloys; carbon-based active materials such as graphite, hard carbon, and soft carbon; oxide-based active materials such as lithium titanate; and Si-based active materials.
[0053] In particular, when the volume expansion rate of the negative electrode active material is large, the effect of the present disclosure that can suppress the increase in battery resistance can be further enjoyed. The volume expansion rate of the negative electrode active material is, for example, 120% or more and 300% or less. As an active material with a large volume expansion rate, Si-based active materials can be cited.
[0054] Si-based active materials are active materials containing Si elements. Examples of Si-based active materials include Si simple substance, Si alloys, and Si oxides. Si alloys preferably contain Si elements as the main component. The proportion of Si elements in Si alloys may be, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. Examples of Si alloys include Si-Al alloys, Si-Sn alloys, Si-In alloys, Si-Ag alloys, Si-Pb alloys, Si-Sb alloys, Si-Bi alloys, Si-Mg alloys, Si-Ca alloys, Si-Ge alloys, and Si-Pb alloys. Si alloys may be two-component alloys or three-component or more alloys. Examples of Si oxides include SiO.
[0055] The shape of the negative electrode active material may be, for example, a particle shape. The average particle size (D 50 ) is, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. 50 ), as described above.
[0056] The negative electrode composite material may contain at least one of a conductive aid and a binder as required. As the conductive aid, for example, a carbon material may be cited. As the carbon material, for example, a particulate carbon material such as acetylene black (AB) and Ketjen black (KB), and a fibrous carbon material such as a carbon fiber, a carbon nanotube (CNT), and a carbon nanofiber (CNF) may be cited.
[0057] Examples of the binder include rubber-based binders such as butadiene rubber (BR), acrylate-butadiene rubber (ABR), and styrene-butadiene rubber (SBR); and fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0058] The negative electrode composite material in the present disclosure may contain a liquid electrolyte (electrolyte) as an electrolyte. When the negative electrode composite material contains an electrolyte, the proportion of the electrolyte relative to the total electrolyte is, for example, 10% by weight or less. As the electrolyte, for example, conventionally known electrolytes that can be used for lithium-ion batteries can be listed.
[0059] C.Battery
[0060] Figure 2 This is a schematic cross-sectional view illustrating a battery in the present disclosure. Figure 2 The battery 10 shown has: a positive electrode active material layer 1, a negative electrode active material layer 2, and an electrolyte layer 3 disposed between the positive electrode active material layer 1 and the negative electrode active material layer 2. In the battery disclosed in the present invention, at least one of the positive electrode active material layer, the negative electrode active material layer and the electrolyte layer contains the above-mentioned solid electrolyte. Figure 2 As shown, the battery 10 generally includes a positive electrode current collector 4 that collects electrons from the positive electrode active material layer 1 , and a negative electrode current collector 5 that collects electrons from the negative electrode active material layer 2 .
[0061] Among them, the battery in the present disclosure may be a battery containing both a solid electrolyte and a liquid electrolyte (electrolyte) as electrolytes. In a battery containing both a solid electrolyte and a liquid electrolyte as electrolytes, the proportion of the electrolyte relative to the total electrolyte is, for example, 10% by weight or less. For the electrolyte, as described in "B. Negative electrode composite material". In addition, the battery in the present disclosure may be a battery containing only a solid electrolyte as an electrolyte, a so-called all-solid battery.
[0062] 1. Positive electrode active material layer
[0063] The positive electrode active material layer contains at least a positive electrode active material. In addition, the positive electrode active material layer may contain at least one of a conductive aid, a binder and an electrolyte as required. The conductive aid and the binder are the same as those described in "B. Negative electrode composite material". In addition, the positive electrode active material layer preferably contains the above-mentioned solid electrolyte as an electrolyte.
[0064] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials, LiMn2O4 and other spinel active materials, LiFePO4 and other olivine active materials. In addition, sulfur (S) can be used as the positive electrode active material. The shape of the positive electrode active material is, for example, a particle shape.
[0065] The thickness of the positive electrode active material layer is not particularly limited, and is, for example, 0.1 μm or more and 1000 μm or less.
[0066] 2. Negative electrode active material layer
[0067] The negative electrode active material layer contains at least a negative electrode active material. In addition, the negative electrode active material layer may contain at least one of a conductive aid, a binder, and an electrolyte as required. In particular, the negative electrode active material layer in the present disclosure preferably contains the above-mentioned negative electrode composite material.
[0068] The thickness of the negative electrode active material layer is not particularly limited, and is, for example, 0.1 μm or more and 1000 μm or less.
[0069] 3. Electrolyte layer
[0070] The electrolyte layer contains at least an electrolyte. In particular, the electrolyte layer preferably contains the above-mentioned solid electrolyte as an electrolyte. In addition, the electrolyte layer may contain a binder and an electrolyte solution as needed. For the binder, as described above. There is no particular limitation on the thickness of the electrolyte layer, for example, it is greater than 0.1 μm and less than 1000 μm.
[0071] 4. Positive electrode collector and negative electrode collector
[0072] Examples of materials for the positive electrode current collector include metals such as aluminum, SUS, and nickel. Examples of materials for the negative electrode current collector include metals such as copper, SUS, and nickel. Examples of shapes for the positive electrode current collector and the negative electrode current collector include foil and mesh.
[0073] 5. Battery
[0074] The battery in the present disclosure may include an outer packaging body that accommodates the above-mentioned components. As the outer packaging body, for example, a laminated outer packaging body and a shell-type outer packaging body can be listed. In addition, the battery in the present disclosure may include a restraining fixture that applies a restraining pressure in the thickness direction to the above-mentioned components. As the restraining fixture, a known fixture can be used. The restraining pressure is, for example, greater than 0.1 MPa and less than 50 MPa, and may be greater than 1 MPa and less than 20 MPa.
[0075] There is no particular limitation on the type of battery in the present disclosure, and typically, it is a lithium-ion secondary battery. There is no particular limitation on the use of the battery, and for example, power sources for vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), electric vehicles (BEV), gasoline vehicles, and diesel vehicles can be cited. In particular, it is preferably used as a driving power source for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) or electric vehicles (BEV). In addition, the battery in the present disclosure can be used as a power source for mobile bodies other than vehicles (such as railways, ships, and aircraft), and can also be used as a power source for electrical products such as information processing devices.
[0076] D. Battery manufacturing method
[0077] The present disclosure can also provide a method for manufacturing a battery, which is a method for manufacturing a battery having a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, the manufacturing method having a negative electrode active material layer forming step of using a negative electrode composite containing a negative electrode active material and an electrolyte to form the negative electrode active material layer, and the electrolyte is the solid electrolyte described above.
[0078] 1. Negative electrode active material layer formation process
[0079] The negative electrode active material layer forming step is a step of forming the negative electrode active material layer using a negative electrode composite material containing a negative electrode active material and an electrolyte. In particular, the above-mentioned solid electrolyte is used as the electrolyte.
[0080] The negative electrode active material, electrolyte and negative electrode composite are as described in "B. Negative electrode composite". The negative electrode active material layer can be formed, for example, by applying a negative electrode slurry containing the above-mentioned negative electrode composite and dispersion medium to a negative electrode collector and drying it. The negative electrode active material layer is as described in "C. Battery".
[0081] 2. Other processes
[0082] The manufacturing method of the battery in the present disclosure may include a positive electrode active material layer forming step, an electrolyte layer forming step, and a laminate forming step (a step of forming a laminate having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer in sequence). For these, methods previously known in the field of batteries can be used. For the positive electrode active material layer and the electrolyte layer, as described in "C. Battery".
[0083] 3. Battery
[0084] The contents of the battery are the same as those described in "C. Battery", so description thereof is omitted.
[0085] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any technical solution having substantially the same structure and achieving the same effect as the technical concept described in the patent claims of the present disclosure is included in the technical scope of the present disclosure.
[0086] Example
[0087] [Example 1]
[0088] (Preparation of sulfide solid electrolyte)
[0089] Li2S, P2S5, LiI and LiBr were mixed to obtain a raw material composition. The raw material composition and tetrahydrofuran 20 times the mass ratio relative to the raw material composition were placed in a glass container and stirred at 25°C for 72 hours. Then, the precipitate was recovered as a precursor of a sulfide solid electrolyte. After the recovered precursor was dried at 25°C under an argon atmosphere, it was calcined at 100°C for 1 hour under atmospheric pressure. The obtained sintered body was vacuum sealed in a quartz tube, the quartz tube was placed in a muffle furnace, and calcined at 160°C for 5 hours. Thus, a sulfide solid electrolyte (a sulfide solid electrolyte of the Li2S-P2S5 system containing LiBr and LiI) was obtained.
[0090] [Example 2 to Example 4 and Comparative Example 1 to Comparative Example 3]
[0091] A sulfide solid electrolyte was prepared in the same manner as in Example 1 except that the firing temperature and firing time in the muffle furnace were changed as shown in Table 1.
[0092] [evaluate]
[0093] (Determination of fracture energy)
[0094] The sulfide solid electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were weighed and compressed to form Figure 1 The pellets shown. The obtained pellets were subjected to a bending test using TENSIRON (manufactured by A&D Co., Ltd.). The bending test conditions were the compression mode of TENSIRON, 0.05 mm / min. The fracture energy was calculated by integrating the stress-strain curve prepared based on the stress (bending stress) and strain (bending strain) obtained from the bending test. The results are shown in Table 1. The stress was calculated by the following formula (1), and the strain was calculated by the following formula (2).
[0095]
Number 1
[0096]
[0097] In formula (1), σ represents bending stress (MPa), b represents the width of the pellet (5 mm), h represents the thickness of the pellet (1 mm), F represents stress (N), and L represents the distance between the supporting points (18.5 mm).
[0098]
Number 2
[0099]
[0100] In formula (2), ε i represents bending strain (%), h represents the thickness of the pellet (1 mm), s represents the deflection (mm), and L represents the distance between the fulcrums (18.5 mm).
[0101] The fracture energy shown in Table 1 is the fracture energy of the pellets with a filling rate of 100% of the sulfide solid electrolyte obtained based on the calibration curve. The calibration curve of filling rate and fracture energy was prepared by preparing three pellets (three pellets with different filling rates) with different pressures for each sulfide solid electrolyte and performing the above-mentioned bending test on the three pellets.
[0102] (Measurement of battery resistance)
[0103] All-solid batteries were prepared as follows using each of the above-mentioned sulfide solid electrolytes for the negative electrode active material layer. The designed capacity of the all-solid battery was 0.3 Ah.
[0104] 18.6 g of negative electrode active material (Si single substance), 8.69 g of the above-mentioned sulfide solid electrolyte, a solution containing styrene butadiene rubber as a binder (the concentration of the binder in the solution is 5% by mass relative to the whole solution) and a solvent (diisobutyl ketone) are added to the Filmix container. Thus, a raw material composition for a negative electrode having a solid content concentration of 43% by mass is obtained. The raw material composition is kneaded using a mixing device (Filmix) to obtain an electrode composition for a negative electrode. A high shear PC wheel is used in Filmix. On the surface of the negative electrode collector (nickel foil), the electrode composition is coated into a film by a blade coating method using a coater, and the film-like electrode composition is heated at 100°C for 30 minutes. Thus, a negative electrode having a negative electrode collector and a negative electrode active material layer is obtained.
[0105] The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) 80.0g, Li2S-P2S5-based sulfide solid electrolyte 9.51g, and conductive aid (VGCF) 2.5g were taken into a Filmix container. Then, a solution containing styrene butadiene rubber as a binder (the concentration of the binder in the solution is 5% by mass relative to the whole solution) and 32.21g of solvent (tetralin) were added to the Filmix container. Thus, a raw material composition for a positive electrode having a solid content concentration of 69% by mass was obtained. The raw material composition was mixed using a mixing device (Filmix) to obtain an electrode composition for the positive electrode. On the surface of the positive electrode collector (aluminum foil), the electrode composition was coated into a film by a blade coating method using a coater, and the film-like electrode composition was heated at 100°C for 30 minutes. Thus, a positive electrode having a positive electrode collector and a positive electrode active material layer was obtained.
[0106] 40g of Li2S-P2S5-based sulfide solid electrolyte, 8.00g of a solution containing acrylate butadiene rubber and hexane (the concentration of acrylate butadiene rubber in the solution is 5% by mass relative to the whole solution), 25.62g of heptane and 8.00g of dibutyl ether were mixed and kneaded with an ultrasonic homogenizer. Thus, a solid electrolyte layer composition was obtained. On the surface of the aluminum foil, the solid electrolyte layer composition was coated into a film by a blade coating method using a coater, and the film-like solid electrolyte layer composition was heated at 100°C for 30 minutes. Thus, a transfer member having a substrate (aluminum foil) and a solid electrolyte layer was obtained.
[0107] The negative electrode and the transfer member are overlapped in a manner that the negative electrode active material layer and the solid electrolyte layer are opposite to each other, and are pressed with 20kN. Then, the aluminum foil is peeled off, and the solid electrolyte layer is transferred on the negative electrode active material layer. Then, the positive electrode is overlapped in a manner that the solid electrolyte layer and the positive electrode active material layer are opposite to each other, and are pressed with 20kN. Thus, a laminate having a negative electrode, a solid electrolyte layer and a positive electrode in sequence is obtained. The laminate is densified with 4 tons / cm, laminated and sealed, thereby making a full solid battery. For the battery produced, a constraint fixture is used and constrained with 5MPa.
[0108] For each of the obtained all-solid batteries, a charge and discharge test was performed. The conditions of the charge and discharge test were set to CCCV charge and discharge with an upper limit voltage of 4.55V and a lower limit voltage of 2.5V, 0.1C, and 1000 cycles. The battery resistance after 1000 cycles was measured. The results are shown in Table 1. In addition, the relationship between the fracture energy and the battery resistance is shown in Figure 3 .
[0109]
Table 1
[0110]
[0111] As shown in Table 1 and Figure 3 As shown, the fracture energy of Examples 1 to 4 is significantly larger than that of Comparative Examples 1 to 3. It is speculated that this is because the solid electrolytes in the embodiments are sintered at a relatively low temperature, so the crystallinity is low and the interface bonding between the solid electrolytes is strong. In addition, in batteries (batteries of Examples 1 to 4) using solid electrolytes with large fracture energy for the negative electrode active material layer, it is speculated that the cracking and peeling of the negative electrode active material layer are suppressed, so the battery resistance is low. In this way, it is confirmed that if it is a solid electrolyte in the present disclosure, the increase in battery resistance can be suppressed.
Claims
1. A solid electrolyte, wherein: The fracture energy when formed into pellets with a length of 5 mm in the X-axis direction, 20 mm in the Y-axis direction, and 1 mm in the Z-axis direction is greater than 21.4×10 3 kJ / m 3 .
2. The solid electrolyte according to claim 1, wherein The fracture energy is 34.2×10 3 kJ / m 3 above.
3. The solid electrolyte according to claim 1, wherein The fracture energy is 75.0×10 3 kJ / m 3 the following.
4. The solid electrolyte according to claim 1, wherein The solid electrolyte is a sulfide solid electrolyte.
5. The solid electrolyte according to claim 4, wherein The sulfide solid electrolyte contains Li element, A element, and S element, and A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In.
6. The solid electrolyte according to claim 4, wherein The sulfide solid electrolyte contains Li element, P element and S element.
7. A negative electrode composite material comprising a negative electrode active material and a solid electrolyte, wherein the solid electrolyte is the solid electrolyte according to any one of claims 1 to 6.
8. The negative electrode composite material according to claim 7, wherein: The negative electrode active material is a Si-based active material.
9. A battery comprising a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, At least one of the positive electrode active material layer, the negative electrode active material layer, and the electrolyte layer contains the solid electrolyte according to any one of claims 1 to 6.
10. A method for manufacturing a battery comprising a positive electrode active material layer, a negative electrode active material layer, and an electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, The manufacturing method comprises a negative electrode active material layer forming step of forming the negative electrode active material layer using a negative electrode composite material containing a negative electrode active material and an electrolyte. The electrolyte is the solid electrolyte according to any one of claims 1 to 6.
Citation Information
Patent Citations
Negative electrode slurry for lithium battery
JP2019125468A